Promiscuous activity of ornithine decarboxylase from Enterobacter hormaechei: An alternative pathway for histamine formation in fermented sausages - Wei He; Binbin Li; Kaidi Hu; Xumei Zhong; Yulin Zhang; Jiamei Yu; Jiaxin Xie; Chengtao Li; Fengqin Li; Lanlan Wu; Shuhong Li; Jianlong Li; et al. (Food Microbiology, 2027)

Spermidine and melatonin ameliorate heat stress-induced decline in sheep semen quality - Shuqi Zou; Can Wang; Bo Pan; Jianpeng Qin; Yinwei Zheng; Kunlin Du; Yaozong Wei; Ao Ning; Xiangyi Chen; Xiaoyue Xiong; Tao Sun; Xiaohui Su; et al. (Theriogenology, 2026)

Spatially assigned dual exciplex architecture for recombination zone localized color stable white OLEDs - Ming-Yu Ye; Wei He; Kai-Ning Tong; Yuan-Yu Zou; Jun Wei; Guodan Wei (Chemical Engineering Journal, 2026)

Decoding glomalin: Mycorrhizal hyphae-secreted glomalin-related soil protein in a zero-carbon background unveils Hsp60 homology and functional molecular architecture - Xiao-Qing Liu; Ci Deng; Li-Jun Zhou; Ying-Ning Zou; Qiang-Sheng Wu (Soil Biology and Biochemistry, 2026)

Exogenous raffinose enhances chilling tolerance in postharvest tomato fruit in relation to the scavenging of ROS, maintenance of energy homeostasis, and cell wall integrity - Weimin Ning; Bingqing Qian; Pan Zou; Yukun Shu; Zhiyuan Wang; Qinlu Zheng; Pan Shu; Yun Zhu; Yuan Qing; Zhong Zhang; Lin Shen (Postharvest Biology and Technology, 2026)

Age-driven shifts in arbuscular mycorrhizal fungal communities associate with bioactive compound accumulation in Polygonum cuspidatum - Zeng-Zheng Zhang; Lu-Lu Meng; Ze-Zhi Zhang; Mashael Daghash Alqahtani; Ying-Ning Zou; Qiang-Sheng Wu (Plant Science, 2026)

High-pressure CO₂ spraying of electret melt-blown polypropylene for piezoelectric self-sensing respiratory monitoring masks - Jiahui Xu; Xiaoyue Zou; Ning Cao; Yunchen Yao; Yuxin Jia; Na Zheng; Zhenshu Chen; Youqiang Yang; Zhanquan Lu; Xiangrong Chen; Pengfei Xie; Cheng Li; et al. (Chemical Engineering Journal, 2026)

Microtopographic differences in CO2 emissions under long-term straw return: The role of microbial resources limitation - Mengmeng Zou; Wantai Yu; Qiang Ma; Yu Ning; Siyu An; Shuo Wang; Zhuqing Xia; Xinhui Zhang; Yun Gao; Mulisa Faji Dida; Shuailin Li (CATENA, 2026)

Reconstruction of satellite remote sensing AOD considering spatial gap filling and downscaling - Xu Chen; Bowen Meng; Yun Peng; Huiyi Xiao; Bin Zou; Shoutao Zhu; Ning Liu; Shenxin Li; Xin Fang (Atmospheric Environment, 2026)

BODIPY with Solvent Polarity and Viscosity Sensitivity for Colorimetric and Fluorescent dual-mode Detection of Cu2+ - Xuejian Xing; Xiaolin Chen; Meng-Die Wu; Ning Zou; Xiazhong Zhang; Wenjun Zhou (Journal of Fluorescence, 2026)

The bidirectional interplay between arbuscular mycorrhizal fungi and root hairs: A review of functional complementarity - Jing-Jing Tan; Yang Lü; Fábio Sérgio Barbosa da Silva; Ying-Ning Zou; Qiang-Sheng Wu; Chun-Yan Liu (Rhizosphere, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Synergistic electrostatic attraction and ion exchange in multi-cationic fibrous adsorbents enabling efficient iodide removal from nuclear medicine wastewater - Junjie Tan; Minjie Chen; Tingxu Xia; Hao Lei; Gaoling Liang; Lianghong Chen; Ning Pan; Hao Zou; Xiaoqin Nie (Chemical Engineering Journal, 2026)

Machine learning-empowered spatial environmental health risk management: Causal inference for sustainable urban agglomeration health equity - Zeduo Zou; Yu Liao; Ye Wang; Ruilin Meng; Yue Gao; Dejian Zhao; Ni Xiao; Ning Liang; Baoyu Chen; Xiuyan Zhao; Xiong He; Hao Yao; et al. (Applied Geography, 2026)

Cellular crosstalk between endothelial and vascular smooth muscle cells via the BACH1/COL3A1 axis promotes vascular calcification in chronic kidney disease - Jing Ning; Sitian Fang; Minzi Qiu; Honghong Zou; Yanxia Chen (Inflammation Research, 2026)

Removal of acetaminophen and total nitrogen from secondary effluent via a UV/PAA-biofilter process: Efficiency, biofilm characteristics, and reaction mechanism - Kun’ao Du; Congwei Luo; Mingshan Yin; Ran Zou; Ning Guo; Yao Xu; Shiqi Bai; Xue Jiang; Xiaoxiang Cheng; Liping Qiu; Daoji Wu; Ruimin Mu (Environmental Research, 2026)

Rhizosphere fungal communities and glomalin-related soil proteins underlie divergent drought responses in indica and japonica rice - Sihan ZHOU; Yanhan JI; Junguo BI; Jiaxuan XU; Jingrui QIU; Xiaoqin ZENG; Zixian JIA; Zijin BIAN; Ning LING; Shuai ZHAO; Sheng ZHOU; Lijun LUO; et al. (Pedosphere, 2026)

A multimodal lateral flow immunoassay driven by a “all-in-one” Au@Pt@ZIF-8 nanocomposite for trace monitoring of 3-phenoxybenzoic acid - Li Ming; Ning Li; Hongyan Zhang; Xiaobo Zou; Can Zhang (Chemical Engineering Journal, 2026)

In-situ heterojunction on high-aspect-ratio cellulose nanocrystals for long-range charge transport in e-skin - Chenchen Shen; Weiwei Chen; Lin Guo; Yanrui Zou; Shuan Han; Ning Yu; Lin Gan; Jin Huang (Carbohydrate Polymers, 2026)

Design of AMPs Targeting BamA as a Potential Target and Research on Their Antimicrobial Mechanisms - Hongyou Chen; Xu Zou; Peiqi Peng; Mingtao Peng; Haoran Liang; Minghe Luo; Tao Wang; Ning Zhang; Qing Zhang; Yuanqiang Wang (Probiotics and Antimicrobial Proteins, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Arbuscular mycorrhizal symbiosis establishes a 14‐3‐3‐centric regulatory hub for integrative drought adaptation in trifoliate orange - Feng-Ling Zheng; Jing-Ling Shi; Zhen Liu; Ying-Ning Zou; Abeer Hashem; Elsayed Fathi Abd_Allah; Qiang-Sheng Wu (Plant Science, 2026)

Corrigendum to “Heap fermentation as a case-based ecological context for interpreting variability in solid-state fermented foods” [Int. J. Food Microbiol. 455 (2026) 111767] - Ning Zhang; Zhihua Li; Xiaowei Huang; Jiyong Shi; Suyi Zhang; Caihong Shen; Songtao Wang; Yongxin Hu; Qian Wang; Xiaobo Zou (International Journal of Food Microbiology, 2026)

Heap fermentation as a case-based ecological context for interpreting variability in solid-state fermented foods - Ning Zhang; Zhihua Li; Xiaowei Huang; Jiyong Shi; Suyi Zhang; Caihong Shen; Songtao Wang; Yongxin Hu; Qian Wang; Xiaobo Zou (International Journal of Food Microbiology, 2026)

Effect of calcium chloride pre-soaking on microbial community and flavor metabolite formation in black bean paste - Qingyu Yang; Dan Yang; Lu Kong; Xiaoming Wang; Lingyun Zhang; Minxin Zou; Chanmin Zheng; Jianting Ning (International Journal of Gastronomy and Food Science, 2026)

An antimicrobial peptide based on tryptophan/arginine minimalist design effectively combating multidrug-resistant bacterial infections via dual mechanisms of action - Jing Zou; Jiahui Wang; Luyang Gao; Jingyi Zhu; Wenjing Xue; Ning Xu; Qiqi Yu; Sanhu Gou; Yun Zhang; Hui Liu; Chao Zhong; Jingman Ni (Chemical Engineering Journal, 2026)

Mapping priority and potential tranquility areas in China using hybrid audio-visual GIS modeling for environment decision making - Xiaoqing Xu; Feiran Hu; Ning Zou; Chumeng Yu; Yue Cao; Xueyao Sun; Zuyao Li; Jialai Meng; Jian Kang (Global Environmental Change, 2026)

Integrated metabolomic and transcriptomic analyses decipher anthocyanin biosynthesis and regulatory mechanisms in novel purple Chimonobambusa purpurea shoots - Hongli Li; Siyao Li; Zhendong Yan; Siyi Liu; Shuliang Liu; Yong Yang; Likou Zou; Aiping Liu; Shujuan Chen; Ning Zhao; Zhongquan Huang; Xiaolin Ao (Food Bioscience, 2026)

Ancient genomes reveal the origins and kinship organisation of Late Bronze Age populations in Northeastern China - Danyang Ge; Ruiqi Zou; Jiaqi Jin; Xiaoxuan Shi; Xiaoming Wang; Di Zhang; Xinghan Zhang; Quanchao Zhang; Chao Ning (Archaeological and Anthropological Sciences, 2026)

Phase separation of the redox sensor RCD1 mediates differential ROS signals to regulate plant growth and stress responses - Jingjing Xing; Kaiwen Li; Wenwen Duan; Zhikun Duan; Yu Zhang; Aiyu Guo; Suting Wang; Ning Ding; Yaling Zou; Xiaobin Wei; Xiaoliang Zhao; Junli Zhang; et al. (Molecular Plant, 2026)

Multisource data fusion framework reveals multi-scale spatiotemporal dynamics of anthropogenic CO2 emissions in China - Shan Xu; Xiya Zhou; Bin Zou; Ning Liu (Journal of Cleaner Production, 2026)

Seasonal response of benthic macroinvertebrate to environmental stressors in mountain streams: Trait convergence and functional homogenization - Mingyang Li; Lunhui Lu; Wenyu Xiao; Wenjuan Ouyang; Yuanyuan Zhang; Yifan Ding; Ning Jia; Xiangxiang Xie; Xi Zou; Peiming Ma; Yanbo Ma; Zhe Li (Aquatic Sciences, 2026)

The miR-140-5p/BMP2 axis mediates T-2 toxin-related injury in both fetal and adult chondrocytes - Bingyu Sun; Yiting Zhao; Fuyuan Li; Ning Zou (Toxicon, 2026)

Life-cycle carbon footprint and mitigation potentials of e-bikes in urban transport systems - Yifei Liu; Qiuxia Zou; Yunchang Ding; Zeguo Yang; Ning Zhang; Ruichang Mao; Huabo Duan; Jiakuan Yang (Resources, Conservation and Recycling, 2026)

Hyphosphere metabolic reprogramming in lipids and aromatic amino acids drives differential mycorrhizal growth promotion in trifoliate orange - Hao-Ran Jiang; Wan-Lin Fu; Ci Deng; Ying-Ning Zou; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Cultivar-dependent effects of arbuscular mycorrhizal (AM) fungal inoculation on fruit quality and native AM fungal community in navel orange - Xin-Ping Tan; Cheng-Zhuo Li; Ying-Ning Zou; An-Qi Lei; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

From laboratory to industrial scale: How to evaluate the carbon mineralization of cement and cement-based materials - Sining Lyu; Qiuxia Zou; Junda Quan; Ning Zhang; Kairui Hu; Lianzheng Gui; Wenbo Yu; Sha Liang; Huabo Duan; Jiakuan Yang (Environmental Impact Assessment Review, 2026)

Advanced technologies of artery-on-a-chip: a review of construction strategies and disease models - Shi-Qi Chang; Li Qiao; Oluwatosin David Abodunrin; Lin Zou; Ning-Ping Huang (Angiogenesis, 2026)

A multiple surrogate simulation-optimization framework for designing pump-and-treat systems - Chaoqi Wang; Zhi Dou; Ning Chen; Yan Zhu; Zhihan Zou; Jian Song; Shen-Huan Lyu (Journal of Contaminant Hydrology, 2026)

Investigation into auto-ignition characteristics and kinetics modeling of PODE2/n-heptane mixtures using an RCM - Xiaochen Wang; Jing Zou; Yingtao Wu; Jianbing Gao; Chenglong Tang; Ning Li; Yuwei Zhao (Fuel, 2026)

Electromagnetic induction–mediated two-stage pyrolysis of tobacco stems for efficient tar cracking and syngas production - Yuxin Yan; Zhenyu Zou; Ning Wang; Yue Pan; Lei Shi; Zhenyu Liu; Qingya Liu (Fuel, 2026)

Soluble lignin: a potential prebiotic modulating gut microbiota and short-chain fatty acid production in in vitro fermentation - Jian Zhu; Qinghao Ning; Tianxing Wang; Zengqi Liu; Long Yu; Hongsheng Liu; Wei Zou (Food Chemistry, 2026)

An improved radiant time series method and its applicability for intermittent air-conditioning systems in office buildings - Quan Zou; Youming Chen; Baisong Ning (Energy and Buildings, 2026)

Skin-inspired wafer-scaled stretchable semiconductor/capacitive proximity sensors for full-skin covering photo-insensitive detection - Jing Sun; Runnan Zou; Huifen Wang; Zihan Yu; Yanhong Tong; Mengfan Zhou; Ning He; Xiaoli Zhao; Qingxin Tang; Yichun Liu (Chemical Engineering Journal, 2026)

First records of Pinuxylon and Xenoxylon wood from the Cretaceous in Shandong Province, Northeast China - Ruiying Hao; Zhanchun Zou; Zikun Jiang; Kemin Xu; Ning Tian; Zhenguo Ning; Aowei Xie; Xiao Shi; Yongdong Wang; Guohua Xu; Fuxia Zhang (Review of Palaeobotany and Palynology, 2026)

MaRAG: a knowledge graph and retrieval-augmented framework for maritime accident analysis - Yingqi Zou; Shaohan Wang; Guanyu Li; Bo Ning (Ocean Engineering, 2026)

Spermidine ameliorates heat stress-induced testicular dysfunction in mice - Shuqi Zou; Tao Sun; Shengqin Zang; Bo Pan; Jianpeng Qin; Can Wang; Kunlin Du; Yaozong Wei; Ao Ning; Xiangyi Chen; Jiangfeng Ye; Yuee Gao; et al. (Journal of Thermal Biology, 2026)

SARCLIP: a multimodal foundation framework for SAR imagery via contrastive language-image pre-training - Chaowei Jiang; Chao Wang; Fan Wu; Peifeng Ma; Lichuan Zou; Tianyang Li; Jing Ning; Yixian Tang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Smartphone-enabled molecularly imprinted paper-based sensor for dual-mode detection of diclofenac sodium in Milk, beef and water - Yongfei Zhou; Ning Li; Xinhua Zhou; Li Ming; Hongyan Zhang; Xiaobo Zou; Can Zhang (Food Research International, 2026)

A universal, accurate natural compounds evaluation platform via cardiomyocyte based biosensing - Jie Chen; Jilin Zheng; Yuli Hu; Ling Zou; Han Yu; Bingyue Zhang; Xuelian Lyu; Hongchun Li; Dongxin Xu; Ning Hu; Yuqun Cai (Chemical Engineering Journal, 2026)

Subchronic exposure to T-2 toxin triggered neurobehavioral damage in developing juvenile rats was associated with oxidative stress and mitochondrial pathway-induced apoptosis of hippocampal neurons - Junfeng Zhou; Fanshuang Meng; Qingwen Li; Hongyu Wang; Ning Zou (Chemico-Biological Interactions, 2026)

Research and Application of the Unsteady Heat Transfer Analytical Model for SAGD - Guoqing Feng; Pan Wang; Xiangjin Liang; Junhui Zou; Aiping Zheng; Ning Li; Dong Song; Yang Liu; Wenzhi Song; Huan Liu; Haiyang Yu (Transport in Porous Media, 2026)

Glycine Alleviates H2O2-Induced Ferroptosis in Mouse Hippocampal Neuron HT22 Cells via the GlyRɑ1/USP35/FPN1 Signaling Pathway - Yinglu Cai; Qiuyu Liang; Weiqin Liu; Zheng Chen; Jialue Liu; Zhenyu Zhang; Zhenyou Zou; Xingcai Ma; Ning Tan; Hua Yao (Molecular Neurobiology, 2026)

Earthworm stress adaptation: The pivotal role of viruses in microplastic‑cadmium co-exposure - Yucui Ning; Yuze Li; Houyu Guo; Jingyang Sun; Jiaqi Xue; Yan Xu; Zhuyun Li; Detang Zou; Dongxing Zhou (Applied Soil Ecology, 2026)

Potassium mercury nitrate loaded silica gel (K2Hg(NO3)4@SiO2) for high-efficiency capture of radioiodine from spent fuel reprocessing off-gas - Gaoling Liang; Lei Liao; Xudong Zhou; Wanjiang You; Jie Wen; Minjie Chen; Weifeng Zhang; Junjie Tan; Hao Lei; Ning Pan; Xiaoqiang Wang; Hao Zou (Chemical Engineering Journal, 2025)

Ultra-stable Pd/NaInY catalyst with atom-dispersed indium modification of NaY zeolite for CO direct esterification to dimethyl carbonate - Yi-Jing Feng; Xiao-Yuan Tan; Jian Lin; Wen-Qiang Zou; Jing Sun; Zhong-Ning Xu; Guo-Cong Guo (Chemical Engineering Journal, 2025)

Comparative analysis of the WRKY gene family between Chimonanthus praecox and C. salicifolius - Wei Zou; Gui-Ting Hu; Fang-Fang Gui; Xin-Chen He; Priyanka Borah; Li Zhu; Hui-Juan Ning; Li-Yuan Yang (Genetica, 2025)

Control of post-harvest soft rot (Rhizopus stolonifer) on sweet cherry using volatile organic compounds produced by Bacillus velezensis Q-84 - Jian-Yu Wang; Min-Xin Mao; Chun-Yan Xu; Man Zou; Wen-Ting Bao; Yi-Ning Zhou; Shun-Qing Hu; Ke-Xin Jiao; Qing-Kun Lu; Peng Zhao; Kun-Peng Zhang; Yi-Lun Chen; et al. (BioControl, 2025)

Self-sustained Bio-Fenton system driven by Shewanella oneidensis for efficient degradation of persistent organic pollutants under oxygen-limited conditions - Yang-Yang Fan; Xuan Yao; Zhi-Yong Li; Xin-Yu Yang; Ming-Juan Zou; Zi-Yi Zhang; Kun Wu; Ting Huang; Ya-Ning Sun; Xiang Xiao (Journal of Hazardous Materials, 2025)

Natural cyclopeptide RA-V eliminates cisplatin-induced senescent cells to circumvent chemoresistance by inhibiting the c-Myc/GLS1 axis - Ying-wei Wu; Zhuang-zhuang Jiang; Jiang-hao Wang; Shu-qing Ye; Wen-long Zou; Ning-hua Tan (Food Bioscience, 2025)

NIR-based chemometric modeling for fermentation round classification and physicochemical indicator prediction during stacking fermentation of sauce-flavor Baijiu - Ning Zhang; Zhihua Li; Xiaowei Huang; Jiyong Shi; Xiaobo Zou; Suyi Zhang; Caihong Shen; Songtao Wang; Yongxin Hu; Qian Wang (Food Bioscience, 2025)

Nanozyme-amplified lateral flow nanobody-immunoassay via PEI-mediated coupling strategy for sensitive detection of 3-phenoxybenzoic acid - Li Ming; Yongfei Zhou; Ning Li; Xinhua Zhou; Hongyan Zhang; Xiaobo Zou; Can Zhang (Food Bioscience, 2025)

Multipath singlet oxygen generation via electron-cycling Cu Ce nanozyme for efficient algae inactivation - Yixin Yao; Gongduan Fan; Antong Shi; Jing Luo; Yuzhou Huang; Rushen Zou; Rongsheng Ning; Kai-qin Xu (Chemical Engineering Journal, 2025)

Modulating the redox states in a 3D conductive MOF for sweat ascorbic acid monitoring - Wei-Qi Wang; Han Xie; Feng Cheng; Ting Zou; Ke-Qiang Xu; Amare Aregahegn Dubale; Wen-Hui Zhang; Ning Xu; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2025)

Archaeobotanical study of the Tangzigou site reveals wild plant exploitation in the terminal Paleolithic of southwest China - Yong-Jiang Huang; Xue-Ping Ji; Nina G. Jablonski; Jian-Hui Liu; Qing Yang; Zi-Ning Zou; Jun Yang; Yun-Heng Ji (Quaternary International, 2025)

Physical protection by soil aggregates drives carbon gains in mangrove restoration: Evidence from coastal aquaculture ponds - Ning Hou; Xiaolei Yin; Weiqi Wang; Xiang Yang; Yuan Li; Yuanchun Zou; Zhaoliang Song; Shaoying Lin; Zhineng Xiao; Rongbin Yin; Fanjiang Zeng; Zhihao Zhang; et al. (Journal of Environmental Management, 2025)

Sensitive dual detection of N-nitrosodiphenylamine and N-nitrosodiethylamine using a PtNPs-enhanced MWCNTs/Fe-porphyrinic MOF nanocomposite-based electrochemical sensor - Jiachen Zhao; Yue Zou; Junlan Yu; Chao Wang; Yili Hu; Fangkai Han; Ning Yang; Fuwei Pi; Ming Zhang; Xiaodan Liu; Jiahua Wang; Huang Dai; et al. (Food Chemistry, 2025)

Moderate ozone application preserves postharvest quality of ‘manaohong’ cherries by enhancing antioxidant defense and membrane stability - Wei Zou; Ning Ji; Yuxin Li; Huali Nie; Qi Gao; Rui Wang; Cunkun Chen; Bangdi Liu (Journal of Stored Products Research, 2025)

Excess vehicular evaporative emissions for prolonged parking during the COVID-19 lockdown in China - Pengfei Song; Jianfei Peng; Yan Liu; Chongzhi Zhong; Qiang Chen; Chao Zou; Shida Sun; Yajun Wu; Yao Gu; Taiyu Zhang; Ning Yang; Hongjun Mao (Journal of Hazardous Materials, 2025)

Cellulose nanocrystal-modified hydrogel wearable sensor with self-healing function from dynamic bond and controllable dual hydrogen-bond crosslinking - Ruihuan Gu; Weiwei Chen; Yanrui Zou; Tingting Yang; Zirui Liu; Ning Yu; Jin Huang; Lin Gan (Carbohydrate Polymers, 2025)

KIAA1522 isoform switching regulates LTR-RTs activity in distinct pluripotency states of hESCs - Ning Yang; Wen Sun; Shiwei Cao; Chen Zhao; Nannan Wang; Pengcheng Li; Yu Zou; Siqi Wang; Tongtong Cui; Shuyu Guo; Wei Li; Haoyi Wang; et al. (Science China Life Sciences, 2025)

QTL analysis of sorghum grain traits based on high-density genetic map - Ning Cao; Yanqing Ding; Jianxia Xu; Bin Cheng; Xu Gao; Wenzhen Li; Guihua Zou; Liyi Zhang (Journal of Applied Genetics, 2025)
Sorghum grain traits are important agronomic traits directly related to yield and are key factors affecting the brewing process of distill liquor. Exploring the genes controlling those traits is of great significance for understanding the genetic mechanism of sorghum grain development. In this study, we conducted genotyping using Super-GBS technology on a recombinant inbred lines (RILs) population derived from the cross between “BTx623” and “Hongyingzi,” consisting of 205 lines. The grain-related traits of the RIL population were investigated in Guiyang, Anshun in Guizhou, and Ledong in Hainan in China. By inclusive composite interval mapping (ICIM) method, a total of 47 quantitative trait locus (QTL) related to four grain traits (thousand grain weight, grain length, grain width, and length–width ratio) were identified across 10 chromosomes. Among them, 20 important QTL were repeatedly detected in multiple traits or environments and distributed on chromosomes 1 (1), 2 (2), 3 (5), 4 (5), 5 (1), 6 (2), 7 (2), 8 (1), and 9 (1). Six candidate genes were identified within the confidence interval of these QTL, and they are homologous to genes controlling rice grain development ( OsMADS1 , RGG2 , OsNST1 , SMG1 , OsGRF8 , and OsAP2-39 ). The results provide a basis for further cloning and functional verification of these candidate genes.

Resource recovery from iodine-containing silver-loaded silica gel: Recycling of silver and immobilization of iodine - Lei Liao; Shilong Song; Gaoling Liang; Xiaoqiang Wang; Ning Pan; Hao Lei; Yongde Zhang; Hao Zou; Jiajia Cheng; Jie Wen; Weifeng Zhang; Tingting Deng (Journal of Hazardous Materials, 2025)

Green catalytic oxidation of m-diethylbenzene to m-ethylacetophenone with molecular oxygen over modified nano-sized TS-1 zeolite - Jinhong Li; Chang Cai; Yi’ning Wang; Zhimei Song; Dan Fang; Nan Zhao; Yue Zhang; Lidong Chen; Jianguo Zhang; Yongcun Zou (Journal of Environmental Chemical Engineering, 2025)

Activation of ROS signaling molecule by AgNPs: molecular mechanisms in roses under abiotic stress, exploration of stress memory, and impact on root microbiota - Meng Zou; Kai Yu; Yu Huang; Qianqian Sheng; Ying Chen; Hao Liu; Zunling Zhu; Ning Feng; Dexing Ma; Dou Dou (Plant and Soil, 2025)

Thermal model for cooling load calculation and its applicability of coincident design weather data generation for intermittent air-conditioning systems - Quan Zou; Youming Chen; Baisong Ning (Energy and Buildings, 2025)

Synergistic effects of low-concentration nanoparticles and Bacillus megaterium on the growth of roses and rhizosphere microbial communities - Meng Zou; Hao Liu; Kai Yu; Ying Chen; Yu Huang; Ning Feng; Jing Bai; Dexing Ma; Guodong Xu; Dou Dou; Han Ma; Yunjiao Han; et al. (Plant and Soil, 2025)

Super-large-scale triaxial tests to study the effect of particle size on dynamic characteristics of gravelly soils - Fanwei Ning; Degao Zou; Gengyao Cui; Jingmao Liu; Duo Li; Yongkui Fu (Bulletin of Engineering Geology and the Environment, 2025)

Identification of Key Biomarkers of Growth-Related Traits in the Bay Scallop Argopecten irradians irradians via Multi-omics Analysis Strategies - Bingyu Ning; Chengda Li; Tanjun Zhao; Yang Zou; Yaoyao Zhan; Yaqing Chang (Marine Biotechnology, 2025)

Differentiation of Citri Reticulatae Pericarpium varieties via HPLC fingerprinting of polysaccharides combined with machine learning - Min-yong Zhong; Meng-ning Li; Wen-shu Zou; Si-qi Hu; Jiang-nan Luo; Qing-xiang Jiang; Qiu-fang Cao; Long-fei Lin; Zhi-xin Wang; Hui Li; Wen-wen Deng (Food Chemistry, 2025)

Urban form regulation for synergetic PM2.5 and O3 control: A multi-indicator constrained DNN simulation - Sha Li; Bin Zou; Ning Liu; Weiwen He; Shenxin Li; Xuying Ma (Science of The Total Environment, 2025)

Synthesis and characterization of Cu-Cu2O/reduced graphene oxide for enhanced iodide adsorption through multiple pathways - Ning Pan; Minjie Chen; Junjie Tan; Lei Liao; Rong Nie; Jianpeng Xu; Run Lei; Hao Zou; Hao Lei; Zhijie Chen; Xiaoqin Nie (Journal of Environmental Chemical Engineering, 2025)

The effect of particle shape on particle breakage and shape evolution in gravelly soils - Fanwei Ning; Degao Zou; Gengyao Cui; Jingmao Liu; Duo Li; Yongkui Fu (Transportation Geotechnics, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Per- and polyfluoroalkyl substances (PFAS) exposure is associated with radioiodine therapy resistance and dedifferentiation of differentiated thyroid cancer - Yongchao Yu; Kang Ning; Xinyu Liu; Yarong Liang; Zan Jiao; Bu Zou; Taonong Cai; Zhongyuan Yang; Weichao Chen; Tong Wu; Mingjie Jiang; Ankui Yang (Environmental Pollution, 2025)

Stem cells vesicles-loaded type I pro-photosensitizer for synergetic oxygen-independent phototheranostics and microenvironment regulation in infected diabetic wounds - Qin Zeng; Ying Zhang; Judun Zheng; Jingyan Lin; Ning Li; Minghai Zhao; Xu Chen; Xipeng Li; Meijiao Zhao; Jialin Huang; Qiulin Xie; Ronghua Yang; et al. (Chemical Engineering Journal, 2025)

Predicting the stress-strain behavior of gravels with a hybrid deep learning approach - Duo Li; Jingmao Liu; Degao Zou; Kaiyuan Xu; Fanwei Ning; Gengyao Cui (Transportation Geotechnics, 2025)

Simultaneous detection of mixed colorants adulterated in black tea based on various morphological SERS sensors - Qingqing Cui; Jingfei Shen; Huiyan Jia; Tiehan Li; Shuci Cao; Shuai Dong; Yuming Wei; Li Zou; Yurong Chen; Yujie Wang; Jingming Ning; Luqing Li (Food Research International, 2025)

A unified soil reaction model for laterally loaded monopiles in soft and stiff clays - Xiuyang Zhang; Degao Zou; Jingmao Liu; Kai Chen; Fanwei Ning; Tianju Wang (Computers and Geotechnics, 2025)

Enhancing structural strength and water retention of crosslinked polyacrylamide gel with the T-ZnOw - Chenwei Zou; Yifei Liu; Ning Yang; Quanmin Luo; Chengwei Mao; Yining Wu; Caili Dai (Fuel, 2024)

Synthesis Pathway Oriented Heterogeneous Stacking Mode of Homogeneous Two-Dimensional Hydrazone-Linked COFs - Zhiying Fan; Yingdan Zhang; Ningning He; Yingdi Zou; Jie Zhang; Chan Deng; Meicheng Zhang; Lei Wang; Ning Liu; Yang Li; Lijian Ma (Chemical Engineering Journal, 2024)

Surface temperature assimilation improving geostationary meteorological satellite surface-sensitive brightness temperature simulations over land - Xin Li; Xiaolei Zou; Mingjian Zeng; Xiaoyong Zhuge; Yang Wu; Ning Wang (Atmospheric Research, 2024)

Exploration of the optimal low-carbon peanut rotation system in South China - Xiaolu Sun; Linjun Qian; Yidan Cao; Minghui Wang; Ning Li; Ruyue Pang; Tong Si; Xiaona Yu; Xiaojun Zhang; Emmanuel Junior Zuza; Xiaoxia Zou (Agricultural Systems, 2024)

Impacts of traffic-signal-based speed guidance system across different application stages on traffic - Bin Sun; Le Hu; Qijun Zhang; Chao Zou; Ning Wei; Zhenyu Jia; Zhong Wu; Hongjun Mao (Transportation Research Part D: Transport and Environment, 2024)

KMT2D deficiency leads to cellular developmental disorders and enhancer dysregulation in neural-crest-containing brain organoids - Ziyun Shan; Yingying Zhao; Xiuyu Chen; Guodong Zhan; Junju Huang; Xuejie Yang; Chongshen Xu; Ning Guo; Zhi Xiong; Fang Wu; Yujian Liu; He Liu; et al. (Science Bulletin, 2024)

Degradation characteristics and effect mechanisms of estrogens during aerobic composting of chicken manure based on the orthogonal test - Ziwei Liang; Junhao Wu; De-Chun He; Yan Li; Yan-Qiu Liang; Jia-Wu Hu; Meng-Yao Zou; Jian-Feng Ning; Wang-Rong Liu (Journal of Environmental Management, 2024)

Cost-efficient breakthrough: Fabricating multifunctional woven hydrogels from water-soluble polyvinyl alcohol yarn - Chenxing Xiang; Yuanhao Tian; Huiming Ning; Ning Hu; Lidan Zhang; Feng Liu; Rui Zou; Shu Wang; Jie Wen; Leilei Li (Chemical Engineering Journal, 2024)

Customizable gradient MXene/polyurethane modules for electromagnetic interference shielding with low reflection and thermal management - Yuhui Feng; Mingye Zhu; Wenjun He; Yan Bai; Ning Ding; Zhen You; Xiang Zou; Weiwei Zhao; Shujuan Liu; Qiang Zhao (Chemical Engineering Journal, 2024)

A self-adaptive memetic algorithm with Q-learning for solving the multi-AGVs dispatching problem - Chang-Zhe Zheng; Hong-Yan Sang; Li-Ning Xing; Wen-Qiang Zou; Lei-Lei Meng; Tao Meng (Swarm and Evolutionary Computation, 2024)

An accurate and efficient forecast framework for fine PM2.5 maps using spatiotemporal recurrent neural networks - Ning Liu; Bin Zou; Yi Li; Zengliang Zang; Shan Xu; Sha Li; Shenxin Li; Lu Zhi; Jun Chen; Fang Zhao (Journal of Cleaner Production, 2024)

Mechanism of aroma formation in white tea treated with solar withering - Li Zou; Caiyan Sheng; Dongzhou Xia; Jixin Zhang; Yuming Wei; Jingming Ning (Food Research International, 2024)

Achieving highly interfacial evaporation rate and continuous salt resistance simultaneously via multi-dimensional composite biomimetic evaporator - Lie Zou; He Zhang; Qian Chen; Size Zheng; Ning Chen; Xiaohu Wu; Xiaoke Li (Chemical Engineering Journal, 2024)

Engineering highly efficient root-inspired microporous layer for high-performance fuel cells - Qinglin Wen; Can He; Fandi Ning; Min Shen; Yiyang Liu; Zhi Chai; Xi Cheng; Xiong Dan; Siyi Zou; Wei Li; Lei He; Bin Tian; et al. (Chemical Engineering Journal, 2024)

Candidate gene analysis of rice grain shape based on genome-wide association study - Wei Xin; Ning Chen; Jiaqi Wang; Yilei Liu; Yifeng Sun; Baojia Han; Xinghua Wang; Zijie Liu; Hualong Liu; Hongliang Zheng; Luomiao Yang; Detang Zou; et al. (Theoretical and Applied Genetics, 2024)

Occurrence, distribution, and ecological risks of antibiotics and antibiotic resistance genes in the surface waters of Gaoyou Lake, China - Xiaojian Xu; Chao Yang; Li Zou; Jun Leng; Ning Wang; Jing Zhang (Environmental Monitoring and Assessment, 2024)

Hypoxia-inducible Factor 1α Contributes to Matrix Metalloproteinases 2/9 and Inflammatory Responses in Periodontitis - Yanyang Ning; Weilan Li; Li Zou; Hongren Shen; Zhijian Su (Cell Biochemistry and Biophysics, 2024)

Rapidly reversible superwettability on textured metallic surfaces - Xianrui Zou; Yongguang Zhang; Wei Fang; Hui Jiang; Zhilu Yang; Qunyang Li; Shuilin Wu; Hongshui Wang; Donghui Wang; Huan Zhou; Tai Yang; Dan Xia; et al. (Chemical Engineering Journal, 2024)

Cyclic cumulative strain of coarse-grained soil under large cyclic stress amplitude - Duo Li; Jingmao Liu; Degao Zou; Fanwei Ning; Chenguang Zhou; Qiuting Jiang (Soil Dynamics and Earthquake Engineering, 2024)

Molecular and radiocarbon constraints on the fate of sedimentary organic carbon in a human-impacted river-dominated ocean margin - Chenglong Wang; Chuchu Zhang; Zhuoyue Zhang; Qihang Liao; Yang Zhang; Ning Wang; Yaping Wang; Xinqing Zou (Marine Geology, 2024)

A wind tunnel study of the effects of vegetation structural characteristics on the airflow field - Ning Jiang; Hong Cheng; Chenchen Liu; Zhiling Fang; Xueyong Zou (CATENA, 2024)

AMF improves response to waterlogging stress in cucumber - Dan Wang; Wei-Jia Wu; Xiao Tian; Nan Xiang; Abeer Hashem; Elsayed Fathi Abd_Allah; Qiang-Sheng Wu; Ying-Ning Zou (Rhizosphere, 2024)

Optimal configuration design of heterogeneous swarm for 3-D cooperative detection based on DOP analysis - Yilin Liu; Shaokun Cai; Minghui Zou; Zhiwen Ning; Zhiming Xiong; Ruihang Yu; Pengfei Jiang (Ocean Engineering, 2024)

Occurrence of ochratoxin A in Sichuan bacon from different geographical regions and characterization and biocontrol of ochratoxigenic Aspergillus westerdijkiae strain 21G2-1A - Kaidi Hu; Keyu Guo; Xingjie Wang; Song Wang; Jianlong Li; Qin Li; Ning Zhao; Aiping Liu; Li He; Xinjie Hu; Yong Yang; Likou Zou; et al. (Food Research International, 2024)

Arbuscular mycorrhizal fungi and rhizobia accelerate plant growth and N accumulation and contribution to soil total N in white clover by difficultly extractable glomalin-related soil protein - Hai-Yang Yu; Wan-Xia He; Ying-Ning Zou; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Applied Soil Ecology, 2024)

Activation of peroxymonosulfate by sludge-derived magnetic biochar for pollutant removal: Performance, applicability, and synergetic mechanism of iron species and carboxylated biochar - Huiping Zeng; Jiaxin Xu; Jianxue Li; Yong Chen; Jing Zou; Ning Liu; Yali Wang; Ruixia Hao; Dong Li; Jie Zhang (Chemical Engineering Journal, 2024)

Lightweight Underwater Object Detection Algorithm for Embedded Deployment Using Higher-Order Information and Image Enhancement - Changhong Liu; Jiawen Wen; Jinshan Huang; Weiren Lin; Bochun Wu; Ning Xie; Tao Zou (Journal of Marine Science and Engineering, 2024)
Underwater object detection is crucial in marine exploration, presenting a challenging problem in computer vision due to factors like light attenuation, scattering, and background interference. Existing underwater object detection models face challenges such as low robustness, extensive computation of model parameters, and a high false detection rate. To address these challenges, this paper proposes a lightweight underwater object detection method integrating deep learning and image enhancement. Firstly, FUnIE-GAN is employed to perform data enhancement to restore the authentic colors of underwater images, and subsequently, the restored images are fed into an enhanced object detection network named YOLOv7-GN proposed in this paper. Secondly, a lightweight higher-order attention layer aggregation network (ACC3-ELAN) is designed to improve the fusion perception of higher-order features in the backbone network. Moreover, the head network is enhanced by leveraging the interaction of multi-scale higher-order information, additionally fusing higher-order semantic information from features at different scales. To further streamline the entire network, we also introduce the AC-ELAN-t module, which is derived from pruning based on ACC3-ELAN. Finally, the algorithm undergoes practical testing on a biomimetic sea flatworm underwater robot. The experimental results on the DUO dataset show that our proposed method improves the performance of object detection in underwater environments. It provides a valuable reference for realizing object detection in underwater embedded devices with great practical potential.

Redox-active phytic acid-based self-assembled hybrid material for enhanced uranium adsorption from highly acidic solution - Hao Lei; Shilong Song; Ning Pan; Hao Zou; Xiaoqiang Wang; Xianguo Tuo (Journal of Hazardous Materials, 2024)

Ionic liquid microwave-assisted hydrodistillation extraction of Angelica sinensis essential oil and its own anti-inflammatory and antioxidant activities - Taotao Li; Huanxian Shi; Wenfei Wang; Jia Li; Tiantian Tang; Yujiao Wang; Ding Liu; Kai Yang; Xuan Wang; Jie Wang; Ning Xia; Jinhui Wang; et al. (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Insights into the precursor specific surface area for engineering Co-free Ni-rich cathodes with tailorable properties - Kangyu Zou; Shangchen Xie; Mingzhu Jiang; Panqing Wang; Tianxiang Ning; Lei Tan; Hongxing Li; Youyuan Zhou; Wanlin Wang; Lingjun Li (Chemical Engineering Journal, 2024)

An Experimental Investigation into Effects of Shale Hydration on Breakdown Pressure and the Fracture Characteristics During Hydraulic Fracture Initiation - Budong Gao; Jianye Mou; Yushi Zou; Shicheng Zhang; Xinfang Ma; Xiaoqiong Wang; Guifu Duan; Ning Li (Rock Mechanics and Rock Engineering, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Diversity and composition of microbial communities in Jinsha earthen site under different degree of deterioration - Jing Li; Yanqiu He; Changjie He; Lin Xiao; Ning Wang; Luman Jiang; Juncheng Chen; Ke Liu; Qiang Chen; Yunfu Gu; Menggen Ma; Xiumei Yu; et al. (Environmental Research, 2024)

A new eudesmane-type sesquiterpene and other constituents from Chloranthus henryi hemsl. var. hupehensis (Pamp.) K.F.Wu and their chemotaxonomic significance - Yun-He Zou; Ning Wang; Hui Yang; Yu-Hang Ban; Huan Liu; Hang Liu; Xiao-Xia Wang; Peng-Yu Zhuang (Biochemical Systematics and Ecology, 2024)

The effect of isolation on laboratory rare minnow (Gobiocypris rarus): Growth, behavior and physiology - Chunsen Xu; Ning Qiu; Fandong Yu; Zhijun Xia; Miaomiao Hou; Qin Wang; Xinhua Zou; Yongfeng He; Chunling Wang; Jianwei Wang (Applied Animal Behaviour Science, 2024)

The non-uniformity characteristics of the evaporation duct in the South China Sea based on CLDAS data - Ning Yang; Xiaohai Zou; Luyao Sun; Debin Su; Tao Wang (Frontiers in Marine Science, 2024)
The non-uniformity of the evaporation duct has a significant impact on the propagation of electromagnetic waves. Based on the near real-time dataset from the China Meteorological Administration Land Data Assimilation System (CLDAS) and the National Centers for Environmental Prediction (NCEP) Climate Forecast System Reanalysis (CFSR) datasets, the non-uniformity characteristics of evaporation duct height (EDH) in the South China Sea (SCS) region at different distances of electromagnetic propagation and the main influencing factors of EDH non-uniformity are analyzed. The findings are given as follows. First, the SCS monsoon has a significant impact on the spatial and temporal distribution of EDH, particularly in the western coastal areas of Luzon Island and the eastern coastal areas of the Indochina Peninsula. Secondly, the non-uniformity of EDH is more pronounced in the western part of Luzon Island, the eastern coast of the Indochina Peninsula, and the sea-land boundary area of the Beibu Gulf. Besides, the non-uniformity of EDH in the western part of Luzon Island and the eastern part of the Indochinese Peninsula is greatly influenced by air-sea temperature difference and relative humidity. Finally, it is advisable to consider the influence of the non-uniformity of EDH when the distance of electromagnetic propagation in coastal areas exceeds 50 km. However, it can be disregarded within a range of 100 km on the broad ocean.

Deciphering survival strategies: Oxidative stress and microbial interplay in Eisenia fetida under tetracycline contamination - Yucui Ning; Siqi Wang; Yuting Sun; Shengwei Zhang; Yifan Wen; Detang Zou; Dongxing Zhou (Science of The Total Environment, 2024)

Predicting peak deviatoric stress of gravels with a novel segmented feature transformation approach - Duo Li; Degao Zou; Jingmao Liu; Kaiyuan Xu; Fanwei Ning; Zhenggang Zhan; Wei Jin (Computers and Geotechnics, 2024)

Ellagic acid promotes osteoblasts differentiation via activating SMAD2/3 pathway and alleviates bone mass loss in OVX mice - Hui Dong; Yuxia Cao; Ke Zou; Qiang Shao; Ronghan Liu; Ying Zhang; Liuzhu Pan; Bin Ning (Chemico-Biological Interactions, 2024)

Cinnamon essential oil based on NLRP3 inflammasome and renal uric acid transporters for hyperuricemia - Xuan Wang; Peijie Zhou; Huanxian Shi; Wenfei Wang; Taotao Li; Tiantian Tang; Jiawei Duan; Jinkai Li; Ning Xia; Jie Wang; Chao Chen; Jinhui Wang; et al. (Food Bioscience, 2023)

Residue dissipation dynamics and dietary risk assessment of emamectin benzoate, chlorantraniliprole, chlorfenapyr, and lufenuron in cabbage - Xiaoyao Wang; Shuai Hu; Lingtao Meng; Kai Wang; Xianxia Zhang; Ke Li; Ning Wang; Nan Zou; Yue Xu; Beixing Li; Wei Mu; Xiuyu Pang (Environmental Science and Pollution Research, 2023)

Mechanistic insights into suppressing microcracks by regulating grain size of precursor for high-performance Ni-rich cathodes - Kangyu Zou; Mingzhu Jiang; Zixiang Zhao; Shangchen Xie; Tianxiang Ning; Lei Tan; Hongxing Li; Youyuan Zhou; Wanlin Wang; Xianwen Wu; Lingjun Li (Chemical Engineering Journal, 2023)

Genome-wide identification and analysis of the evolution and expression pattern of the SBP gene family in two Chimonanthus species - Ge-Ge Jiang; Qian-Qian Wan; Wei Zou; Gui-Ting Hu; Li-Yuan Yang; Li Zhu; Hui-Juan Ning (Molecular Biology Reports, 2023)

Effects of acute and chronic thermal stress on survival, apoptosis, and transcriptional responses of Scapharca broughtonii - Desheng Zou; Weian Cao; Guilong Liu; Junhao Ning; Xia Lu; Jinjing Wang; Min Chen; Bo Liu; Jinsheng Zhang; Chunde Wang (Journal of Oceanology and Limnology, 2023)

Microplastic pollution and the related ecological risks of organic composts from different raw materials - Jiajia Zhang; Ning Guo; Wencheng Ding; Bao Han; Meng Zhao; Xuexia Wang; Jiachen Wang; Bing Cao; Guoyuan Zou; Yanhua Chen (Journal of Hazardous Materials, 2023)

The effects of environmental empathy and sustainable intelligence on wetland tourists’ revisit intention using an extended model of goal-directed behavior - Guoyi Chen; Mingxuan Zou; Ning Ran; Bangquan Yan; Shangkang Li (Journal of Cleaner Production, 2023)

Real world emission characteristics of Chinese fleet and the current situation of underestimated ship emissions - Lei Yang; Qijun Zhang; Zongyan Lv; Jingbo Zhao; Chao Zou; Ning Wei; Zhenyu Jia; Yanjie Zhang; Fei Fu; Jianhua Lv; Lin Wu; Ting Wang; et al. (Journal of Cleaner Production, 2023)

Study on detection method of microplastics in farmland soil based on hyperspectral imaging technology - Lijia Xu; Yanjun Chen; Ao Feng; Xiaoshi Shi; Yanqi Feng; Yuping Yang; Yuchao Wang; Zhijun Wu; Zhiyong Zou; Wei Ma; Yong He; Ning Yang; et al. (Environmental Research, 2023)

Hollow self-assembled hybrid framework based on phytic acid for U(VI) capture from highly acidic aqueous media - Hao Lei; Ning Pan; Hao Zou; Xiaoqiang Wang; Xianguo Tuo (Chemical Engineering Journal, 2023)

Improving air quality through urban form optimization: A review study - Sha Li; Bin Zou; Xuying Ma; Ning Liu; Zixin Zhang; Manman Xie; Lu Zhi (Building and Environment, 2023)

Seismogenic structure of the 2020 Jiashi, Xinjiang Ms 5.4 and Ms 6.4 moderate earthquakes - Shan-Shan Liang; Guang-Wei Zhang; Xiao-Ning Huang; Li-Ye Zou; Yan-Qiong Liu; Yun-Da Ji (Applied Geophysics, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Zebrafish SETD3 mediated ubiquitination of phosphoprotein limits spring viremia of carp virus infection - Xin Zhao; Ning Ji; Jiahong Guo; Wenji Huang; Jianhua Feng; Yanjie Shi; Kangyong Chen; Junya Wang; Jun Zou (Fish & Shellfish Immunology, 2023)

Ultrasonic-assisted self-assembly of a neodymium vanadate and hydroxylated multi-walled carbon nanotubes composite for electrochemical detection of p-nitrophenol - Ya You; Shuang-Ning Li; Jiao Zou; Ya-Nan Xin; Sui Peng; Bo Liu; Xin-Yu Jiang; Jin-Gang Yu (Process Safety and Environmental Protection, 2023)

Effect of stress amplitude on mechanical and acoustic emission of sandstone under constant–cyclic loading - Bichuan Zhang; Yunpei Liang; Zhanyi Zhao; Quanle Zou; Haolong Zheng; Yanhao Ning; Fanjie Kong; Qican Ran (Bulletin of Engineering Geology and the Environment, 2023)

Study on the evolutionary process of interbedded anti-inclined slope block-flexure toppling in the upper Yalong River - Bocheng Zhang; Yibing Ning; Huiming Tang; Bingdong Ding; Kun Fang; Zongxing Zou (Bulletin of Engineering Geology and the Environment, 2023)

A visual bi-layer indicator based on mulberry anthocyanins with high stability for monitoring Chinese mitten crab freshness - Xiaowei Huang; Liuzi Du; Zhihua Li; Jin Xue; Jiyong Shi; Haroon Elrasheid Tahir; Xiaodong Zhai; Junjun Zhang; Ning Zhang; Wei Sun; Xiaobo Zou (Food Chemistry, 2023)

The optimal speed model based on minimum temporal and spatial energy consumption - Bin Sun; Qijun Zhang; Chao Zou; Ning Wei; Zhenyu Jia; Zhong Wu; Hongjun Mao; Yi Zhang (Environmental Science and Pollution Research, 2023)

A method to study the effects of combined stress of cadmium and microplastics on the acute toxicity of Eisenia fetida - Yucui Ning; Haoran Zhou; Xu Wang; Jiyang Lu; Yanna Yang; Detang Zou; Dongxing Zhou (Environmental Science and Pollution Research, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

GWAS of grain color and tannin content in Chinese sorghum based on whole-genome sequencing - Liyi Zhang; Jianxia Xu; Yanqing Ding; Ning Cao; Xu Gao; Zhou Feng; Kuiying Li; Bing Cheng; Lengbo Zhou; Mingjian Ren; Yuezhi Tao; Guihua Zou (Theoretical and Applied Genetics, 2023)
Key message Seventy-three QTL related to grain color and tannin content were identified in Chinese sorghum accessions, and a new recessive allelic variant of TAN2 gene was discovered. Abstract Sorghum is mainly used for brewing distilled liquors in China. Since grain tannins play an important role in liquor brewing, accurately understanding the relationship between grain color and tannin content can provide basis for selection standards of tannin sorghum . We resequenced a panel of 242 Chinese sorghum accessions and performed population structure and genome-wide association study (GWAS) to identify quantitative trait locus (QTL) affecting pericarp color, testa pigment, and tannin content. Phylogenetic analysis, principal component analysis (PCA), and admixture model were used to infer population structure. Two distinct genetic sub-populations were identified according to their corresponding northern and southern geographic origin. To investigate the genetic basis of natural variation in sorghum grain color, GWAS with 2,760,264 SNPs was conducted in four environments using multiple models (Blink, FarmCPU, GLM, and MLM). Seventy-three QTL were identified to be associated for the color of exocarp, mesocarp, testa, and tannin content on all chromosomes except chromosome 5, of which 47 might be novel QTL. Some important QTL were found to colocalize with orthologous genes in the flavonoid biosynthetic pathway from other plants, including orthologous of Arabidopsis ( Arabidopsis thaliana ) TT2 , TT7 , TT12 , TT16 and AT5G41220 ( GST ), as well as orthologous of rice ( Oryza sativa ) MYB61 and OsbHLH025 . Our investigation of the variation in grain color and tannin content in Chinese sorghum germplasm may help guide future sorghum breeding for liquor brewing.

Organic matter pore characteristics of over-mature marine black shale: a comparison of organic fractions with different densities - Shitan Ning; Peng Xia; Niuniu Zou; Yi Zhong; Yin Yu; Yuliang Mou; Ke Wang (Frontiers of Earth Science, 2023)

Real-time and accurate detection of citrus in complex scenes based on HPL-YOLOv4 - Lijia Xu; Yihan Wang; Xiaoshi Shi; Zuoliang Tang; Xinyuan Chen; Yuchao Wang; Zhiyong Zou; Peng Huang; Bi Liu; Ning Yang; Zhiwei Lu; Yong He; et al. (Computers and Electronics in Agriculture, 2023)

Evaluating traffic emission control policies based on large-scale and real-time data: A case study in central China - Chao Zou; Lin Wu; Yanan Wang; Shida Sun; Ning Wei; Bin Sun; Jingwei Ni; Jing He; Qijun Zhang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2023)

0D/2D CeO2/BiVO4 S-scheme photocatalyst for production of solar fuels from CO2 - Jiguo Geng; Shixun Guo; Zongyan Zou; Zhenzhou Yuan; Dong Zhang; Xiaotong Yan; Xuefeng Ning; Xiujun Fan (Fuel, 2023)

IL-27 suppresses spring viremia of carp virus replication in zebrafish - Yanjie Shi; Kangyong Chen; Xin Zhao; Yanan Lu; Wenji Huang; Jiahong Guo; Ning Ji; Zhao Jia; Hehe Xiao; Huifeng Dang; Jun Zou; Junya Wang (Fish & Shellfish Immunology, 2023)

Terpenoids from the roots of Chloranthus henryi Hemsl. var. hupehensis (Pamp.) K. F. Wu and their chemotaxonomic significance - Shuai Liu; Zi-Mo Zhang; Hui Yang; Yun-He Zou; Ning Wang; Peng-Yu Zhuang; Xiao-Xia Wang; Hang Liu (Biochemical Systematics and Ecology, 2023)

MiR-140 is involved in T-2 toxin-induced matrix degradation of articular cartilage - Yaning Shi; Xinhua Shao; Mengyi Sun; Jing Ma; Bingsu Li; Ning Zou; Fuyuan Li (Toxicon, 2023)

Investigation into shale softening induced by water/CO2-rock interaction - Ning Li; Zhijun Jin; Haibo Wang; Yushi Zou; Shicheng Zhang; Fengxia Li; Tong Zhou; Minqu Jiang (International Journal of Rock Mechanics and Mining Sciences, 2023)

Salt Bridge-intermediated three phase decoupling electrolytes for high voltage electrolytic aqueous Zinc-Manganese dioxides battery - Qi Xu; Qi-Xing Xie; Tong Xue; Gao Cheng; Jian-Dong Wu; Lan Ning; Xiang-Hui Yan; You-Jun Lu; Zhong-Li Zou; Bei-Ping Wang; Feng-Lan Han (Chemical Engineering Journal, 2023)

A high-efficient and low-consumption nanoimprint method to prepare large-area and high-quality Nafion array for the ordered MEA of fuel cell - Yali Li; Qinglin Wen; Jiaqi Qin; Siyi Zou; Fandi Ning; Chuang Bai; Saifei Pan; Hanqing Jin; Pengpeng Xu; Min Shen; YuJiang Song; Xiaochun Zhou. (Chemical Engineering Journal, 2023)

Detection and assessment of dust mite allergens in an indoor environment in Anhui, China - Qiqi Xue; Minghui Zou; Junjie Guo; Qiao Teng; Qiqi Zhang; Lingwei Sheng; Sijia Xu; Can Fang; Ning Yao; Yuanyuan Li; Jinhong Zhao (Environmental Science and Pollution Research, 2023)
Dust in the home environment is thought to be a potential trigger for increasing allergic diseases, such as allergic rash, rhinitis, asthma, and other conditions, associated with dust mites. To verify the status of dust mite prevalence in indoor surroundings, we collected 189 dust samples from the air conditioner filters ( n = 75) and floors ( n = 114) of households, schools, and hotels in the Anhui area, China. All samples were measured for dust mite breeding rate and breeding density under light microscopy and analyzed for dust mite species Dermatophagoides farinae 1 (Der f 1) and Dermatophagoides pteronyssinus 1 (Der p 1) allergen using enzyme-linked immunosorbent assay (ELISA). The dust mite breeding rates were 34.67% (26/75) and 20.18% (23/114), respectively, in the dust samples from the floor and air conditioning filters. The breeding density was the highest in households (10/g), followed by schools (9/g) and hotels (4/g). ELISA indicated that the allergen threshold (2.0 µg/g dust) of Der f 1 was exceeded in only two samples and Der p 1 in one sample. Additionally, a questionnaire was used to investigate the health knowledge on allergic diseases involved in indoor facilities, finding that most allergy sufferers were aware that indoor dust might be responsible for their conditions. The findings suggest that regular maintenance of indoor hygiene and cleaning of air-conditioning filters should reduce the risks of exposure to indoor allergens.

Investigation into a homogenous step-like rock slope response under wide-frequency seismic loads using a large-scale shaking table - Jianxian He; Zhifa Zhan; Shengwen Qi; Chunlei Li; Bowen Zheng; Guoxiang Yang; Songfeng Guo; Xiaolin Huang; Yu Zou; Ning Liang (Natural Hazards, 2022)

Crustal electrical structure across the Tangra-Yumco tectonic belt revealed by magnetotelluric data: new insights on the east–west extension mechanism of the Tibetan plateau - Ning Chen; Xuben Wang; Changsheng Shao; Jun Zou; Zhengwei Xu; Dewei Li; Xiangpeng Wang (Acta Geophysica, 2022)

Effects of elevated pCO 2 on the response of coccolithophore Emiliania huxleyi to prolonged darkness - Letian Gao; Zhongjian Huang; Zhihai Zhong; Xiaomeng Shi; Xing Chang; Yuhong Sun; Nuoyan Zhang; Ning Zou; Shanying Tong (Marine Biology Research, 2022)

Review and prospect of research on road traffic flow energy model - Bin Sun; Qijun Zhang; Chao Zou; Hui Tong; Ning Wei; Zhenyu Jia; Hongjun Mao (Environmental Science and Pollution Research, 2022)

Residual analysis of QoI fungicides in multiple (six) types of aquatic organisms by UPLC-MS/MS under acutely toxic conditions - Hong Li; Shuai Hu; Fengshou Sun; Qi Sun; Ning Wang; Beixing Li; Nan Zou; Jin Lin; Wei Mu; Xiuyu Pang (Environmental Science and Pollution Research, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Physiological and Transcriptional Responses to Acute and Chronic Thermal Stress in the Ark Shell Scapharca subcrenata - Desheng Zou; Junhao Ning; Xia Lu; Xia Wang; Min Chen; Bo Liu; Jun Fang; Chunde Wang (Frontiers in Marine Science, 2021)
Ark shells ( Scapharca subcrenata ) grown on the tidal flats are often exposed to high temperature stresses in summer. In order to better understand their adaption to extreme or natural high temperature, we first determined the 96-h upper lethal temperature of ark shell and then investigated their physiological and transcriptional responses to acute or chronic thermal stress at the 96-h upper median lethal temperature (32°C). A significantly higher cumulative mortality (52% in 96 h) was observed in the acute heating treatment (AHT) group than that (22% in 7 days) in the chronic heating treatment (CHT) group. The apoptosis and necrosis rates of hemocytes were increased significantly in a time-dependent manner under both thermal stress strategies. Activities of antioxidant enzymes [superoxide dismutase (SOD) and catalase (CAT)] increased dramatically in a short time followed by a quick decline and reached to a lower level within 12 h in the AHT group, but maintain relatively high levels over a long period in the CHT group. The contents of malondialdehyde (MDA) were increased significantly firstly and restored to the original later in both acute and chronic thermal stress. Moreover, expression of the genes related to heat shock proteins (HSPs; HSP90 , HSP70 , HSP20 , and sHSP ), apoptosis [TNF receptor-associated factor 6 ( TRAF6 ), glucose regulated protein 78 kD ( GRP78 ), and caspase-3 ( Casp- 3)] and antioxidant responses [glutathione S-transferase ( GST ) and multidrug resistance protein ( MRP )] could be induced and up-regulated significantly by thermal stress, however, expression of regucalcin ( RGN ), metallothionein ( MT ), and peroxiredoxin ( PRX ) was down-regulated dramatically under the two heating treatments. These results suggested that anti-apoptotic system, antioxidant defense system and HSPs could play important roles in thermal tolerance of ark shells, and the heat-resistant ark shell strains could be selected continuously by properly chronic thermal stress.

Thermal Shock Effect on Acoustic Emission Response During Laboratory Hydraulic Fracturing in Laizhou Granite - Ning Li; Shicheng Zhang; Haibo Wang; Shan Wu; Yushi Zou; Xinfang Ma; Tong Zhou (Rock Mechanics and Rock Engineering, 2021)

Seismic response characteristics and deformation evolution of the bedding rock slope using a large-scale shaking table - Jianxian He; Shengwen Qi; Zhifa Zhan; Songfeng Guo; Chunlei Li; Bowen Zheng; Xiaolin Huang; Yu Zou; Guoxiang Yang; Ning Liang (Landslides, 2021)

Exploring arbuscular mycorrhizal symbiosis in wetland plants with a focus on human impacts - Guang-Ming Huang; A. K. Srivastava; Ying-Ning Zou; Qiang-Sheng Wu; Kamil Kuča (Symbiosis, 2021)

Mycorrhiza-induced plant defence responses in trifoliate orange infected by Phytophthora parasitica - Li Tian; Ying-Ning Zou; Qiang-Sheng Wu; Kamil Kuča (Acta Physiologiae Plantarum, 2021)

The contrasting effects of thermodynamic and dynamic processes on East Asian summer monsoon precipitation during the Last Glacial Maximum: a data-model comparison - Yong Sun; Haibin Wu; Masa Kageyama; Gilles Ramstein; Laurent Z. X. Li; Ning Tan; Yating Lin; Bo Liu; Weipeng Zheng; Wenchao Zhang; Liwei Zou; Tianjun Zhou (Climate Dynamics, 2021)
The Last Glacial Maximum (LGM; 21 ka BP) was the most recent glacial period when the global ice sheet volume was at a maximum. Therefore, the LGM can be used to investigate atmospheric dynamics under a climate that differed significantly from the present. This study quantitatively compares pollen records of boreal summer (June–July–August) precipitation with the PMIP3 LGM simulations. The data-model comparison shows an overall agreement on a drier than pre-industrial East Asian summer monsoon (EASM) climate. Nevertheless, 17 out of 55 records show a regional precipitation increase that is also simulated over the additional land mass area due to sea level drop. The thermodynamic and dynamic responses are analyzed to explain a drier LGM EASM as a combination of these two antagonistic mechanisms. Relatively low atmospheric moisture content was the main thermodynamic control on the lower LGM (relative to pre-industrial levels) EASM precipitation amounts in both the reconstructions and the models. In contrast, two dynamic processes in relation to stationary eddy activity act to increase EASM precipitation regionally in records and simulations, respectively. Precipitation increase in records is explained by dynamic enhancement of the horizontal moisture transport, while dynamic enhancement of the vertical moisture transport leads to simulated precipitation increase over the specific region where landmass was exposed during LGM along continental coastlines of China due to significant drop in sea level (relative to pre-industrial levels). Overall, the opposing effects of thermodynamic and dynamic processes on precipitation during the LGM provide a means to reconcile the spatial heterogeneity of recorded precipitation changes in sign, although data-model comparison suggests that the simulated dynamic wetting mechanism is too weak relative to the thermodynamic drying mechanism over data-model disagreement regions.

Experimental Study of the Simultaneous Initiation of Multiple Hydraulic Fractures Driven by Static Fatigue and Pressure Shock - Bo Zeng; Detang Lu; Yushi Zou; Jiawei Zhou; Sihai Li; Ning Li; Zhigang Cao (Rock Mechanics and Rock Engineering, 2020)

The temperature distribution model and its application to reservoir depth prediction in fault-karst carbonate reservoirs - Jian Lei; Baozhi Pan; Yuhang Guo; Yufei Fan; Yandong Xu; Ning Zou (Arabian Journal of Geosciences, 2020)

Thermal Effects on the Physical and Mechanical Properties and Fracture Initiation of Laizhou Granite During Hydraulic Fracturing - Ning Li; Xinfang Ma; Shicheng Zhang; Yushi Zou; Shan Wu; Sihai Li; Zhaopeng Zhang; Tong Cao (Rock Mechanics and Rock Engineering, 2020)

Coupled Physical–Chemical Effects of CO2 on Rock Properties and Breakdown During Intermittent CO2-Hybrid Fracturing - Sihai Li; Shicheng Zhang; Xinfang Ma; Yushi Zou; Ning Li; Shan Wu; Zhaopeng Zhang (Rock Mechanics and Rock Engineering, 2020)

Correction to: Whole Exome Sequencing Identifies Two Novel Mutations in the Reticulon 4–Interacting Protein 1 Gene in a Chinese Family with Autosomal Recessive Optic Neuropathies - Xiao-Huan Zou; Xin-Xin Guo; Hui-Zhen Su; Chong Wang; En-Lin Dong; Ning Wang; Wan-Jin Chen; Qi-Jie Zhang (Journal of Molecular Neuroscience, 2020)

Feasible Green Strategy for the Quantitative Bioaccumulation of Heavy Metals by Lemna minor: Application of the Self-Thinning Law - Yuan Sun; Peike Gao; Ning Ding; Xiaoming Zou; Yiliang Chen; Taihua Li; Wang Cuiting; Xuan Xu; Tingting Chen; Honghua Ruan (Bulletin of Environmental Contamination and Toxicology, 2020)

Establishment and characterization of immortalized porcine neonatal hepatocytes without the use of viral components - Yunlong Zou; Haiyang Hao; Ning Li; Qiuyan Li (In Vitro Cellular & Developmental Biology - Animal, 2020)

Repellent activities of essential oils rich in sesquiterpenoids from Saussurea amara (L.) DC. and Sigesbeckia pubescens Makino against two stored-product insects - Zhi-Hua Li; Yang Wang; Jian-Sheng Sun; Ji-Gang Li; Ke-Xing Zou; Hong Liu; Gui-Xiang Li; Zhi-Zhong Hu; Li-Zheng Nong; Zhen-Xing Ning; Yan Wu; Shu-Shan Du (Environmental Science and Pollution Research, 2019)

Hydraulic Fractures Induced by Water-/Carbon Dioxide-Based Fluids in Tight Sandstones - Sihai Li; Shicheng Zhang; Xinfang Ma; Yushi Zou; Ning Li; Ming Chen; Tong Cao; Zhenkai Bo (Rock Mechanics and Rock Engineering, 2019)

Characteristics of grain size distribution and the shear strength analysis of Chenjiaba long runout coseismic landslide - Ephrem Getahun; Sheng-wen Qi; Song-feng Guo; Yu Zou; Ning Liang (Journal of Mountain Science, 2019)

Whole Exome Sequencing Identifies Two Novel Mutations in the Reticulon 4–Interacting Protein 1 Gene in a Chinese Family with Autosomal Recessive Optic Neuropathies - Xiao-Huan Zou; Xin-Xin Guo; Hui-Zhen Su; Chong Wang; En-Lin Dong; Ning Wang; Wan-Jin Chen; Qi-Jie Zhang (Journal of Molecular Neuroscience, 2019)

Quantifying the carbon source of pedogenic calcite veins in weathered limestone: implications for the terrestrial carbon cycle - Lin Zou; Lin Dong; Meng Ning; Kangjun Huang; Yongbo Peng; Shujian Qin; Honglin Yuan; Bing Shen (Acta Geochimica, 2019)

Hydrogen Sulfide Inhibits Formaldehyde-Induced Senescence in HT-22 Cells via Upregulation of Leptin Signaling - Wei-Wen Zhu; Min Ning; Yi-Zhu Peng; Yi-Yun Tang; Xuan Kang; Ke-Bin Zhan; Wei Zou; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2019)

Identification of proteins differentially expressed in the gills of grass carp (Ctenopharyngodon idella) after hypoxic stress by two-dimensional gel electrophoresis analysis - Zhan-Ning Xu; Guo-Dong Zheng; Cheng-Bin Wu; Xia-Yun Jiang; Shu-Ming Zou (Fish Physiology and Biochemistry, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Sono-advanced Fenton-like degradation of aromatic amines in textile dyeing sludge: efficiency and mechanisms - Haiyuan Zou; Xun-an Ning; Yi Wang; Jian Sun; Yanxiang Hong (Environmental Science and Pollution Research, 2019)

Organic-rich source rock characterization and evaluation of the Cretaceous Qingshankou Formation: results from geophysical logs of the second scientific drilling borehole in the Songliao Basin, NE China - Xiaohuan Zhang; Changchun Zou; Jinhuan Zhao; Ning Li; Shuxia Zhang; Kouamelan Serge Kouamelan; Liang Xiao; Huolin Ma; Yixiong Niu (Geosciences Journal, 2019)

Acoustic Emission Response of Laboratory Hydraulic Fracturing in Layered Shale - Ning Li; Shicheng Zhang; Yushi Zou; Xinfang Ma; Zhaopeng Zhang; Sihai Li; Ming Chen; Yueyue Sun (Rock Mechanics and Rock Engineering, 2018)

Combined ultrasound with Fenton treatment for the degradation of carcinogenic polycyclic aromatic hydrocarbons in textile dying sludge - Jian-Hao Zhang; Hai-Yuan Zou; Xun-An Ning; Mei-Qing Lin; Chang-Min Chen; Tai-Cheng An; Jian Sun (Environmental Geochemistry and Health, 2018)

Experimental Analysis of Hydraulic Fracture Growth and Acoustic Emission Response in a Layered Formation - Li Ning; Zhang Shicheng; Zou Yushi; Ma Xinfang; Wu Shan; Zhang Yinuo (Rock Mechanics and Rock Engineering, 2018)

RNA-Seq analysis reveals the distinctive adaxial–abaxial polarity in the asymmetric one-theca stamen of Canna indica - Xueyi Tian; Pu Zou; Mingzhi Miao; Zulin Ning; Jingping Liao (Molecular Genetics and Genomics, 2018)

Development and trait evaluation of chromosome single-segment substitution lines of O. meridionalis in the background of O. sativa - Ning He; Rouxian Wu; Xiaoping Pan; Liping Peng; Kang Sun; Tuo Zou; Haitao Zhu; Ruizhen Zeng; Ziqiang Liu; Guifu Liu; Shaokui Wang; Guiquan Zhang; et al. (Euphytica, 2017)

Mapping stripe rust resistance gene YrZH22 in Chinese wheat cultivar Zhoumai 22 by bulked segregant RNA-Seq (BSR-Seq) and comparative genomics analyses - Yong Wang; Jingzhong Xie; Huaizhi Zhang; Bingmin Guo; Shunzong Ning; Yongxing Chen; Ping Lu; Qiuhong Wu; Miaomiao Li; Deyun Zhang; Guanghao Guo; Yan Zhang; et al. (Theoretical and Applied Genetics, 2017)

Hydraulic Fracture Growth in a Layered Formation based on Fracturing Experiments and Discrete Element Modeling - Zou Yushi; Ma Xinfang; Zhou Tong; Li Ning; Chen Ming; Li Sihai; Zhang Yinuo; Li Han (Rock Mechanics and Rock Engineering, 2017)

Differential immune responses of Monochamus alternatus against symbiotic and entomopathogenic fungi - Wei Zhang; Jie Meng; Jing Ning; Peijun Qin; Jiao Zhou; Zhen Zou; Yanhong Wang; Hong Jiang; Faheem Ahmad; Lilin Zhao; Jianghua Sun (Science China Life Sciences, 2017)
Monochamus alternatus , the main vector beetles of invasive pinewood nematode, has established a symbiotic relationship with a native ectotrophic fungal symbiont, Sporothrix sp. 1, in China. The immune response of M. alternatus to S. sp. 1 in the coexistence of beetles and fungi is, however, unknown. Here, we report that immune responses of M. alternatus pupae to infection caused by ectotrophic symbiotic fungus S . sp. 1 and entomopathogenic fungus Beauveria bassiana differ significantly. The S . sp. 1 did not kill the beetles while B. bassiana killed all upon injection. The transcriptome results showed that the numbers of differentially expressed genes in M. alternatus infected with S . sp. 1 were 2-fold less than those infected with B. bassiana at 48 hours post infection. It was noticed that Toll and IMD pathways played a leading role in the beetle’s immune system when infected by symbiotic fungus, but upon infection by entomopathogenic fungus, only the Toll pathway gets triggered actively. Furthermore, the beetles could tolerate the infection of symbiotic fungi by retracing their Toll and IMD pathways at 48 h. This study provided a comprehensive sequence resource of M. alternatus transcriptome for further study of the immune interactions between host and associated fungi.

Heat shock transcription factor 1 protects against pressure overload-induced cardiac fibrosis via Smad3 - Ning Zhou; Yong Ye; Xingxu Wang; Ben Ma; Jian Wu; Lei Li; Lin Wang; Dao Wen Wang; Yunzeng Zou (Journal of Molecular Medicine, 2017)

Mycorrhiza alters the profile of root hairs in trifoliate orange - Qiang-Sheng Wu; Chun-Yan Liu; De-Jian Zhang; Ying-Ning Zou; Xin-Hua He; Qing-Hua Wu (Mycorrhiza, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Biosorption and bioaccumulation of thallium by thallium-tolerant fungal isolates - Jialong Sun; Xiao Zou; Tangfu Xiao; Yanlong Jia; Zengping Ning; Min Sun; Yizhang Liu; Tao Jiang (Environmental Science and Pollution Research, 2015)

Serum Levels of Copper and Zinc in Patients with Rheumatoid Arthritis: a Meta-analysis - Lihong Xin; Xiao Yang; Guoqi Cai; Dazhi Fan; Qing Xia; Li Liu; Yanting Hu; Ning Ding; Shengqian Xu; Li Wang; Xiaona Li; Yanfeng Zou; et al. (Biological Trace Element Research, 2015)

Increased Expression of p-Akt correlates with Chronic Allograft Nephropathy in a Rat Kidney Model - Li-Na Zhou; Ning Wang; Yang Dong; Yiqin Zhang; Hequn Zou; Qingqin Li; Yangling Shi; Ling Chen; Wenying Zhou; Conghui Han; Yuxin Wang (Cell Biochemistry and Biophysics, 2015)

Mycorrhiza-induced lower oxidative burst is related with higher antioxidant enzyme activities, net H2O2 effluxes, and Ca2+ influxes in trifoliate orange roots under drought stress - Ying-Ning Zou; Yong-Ming Huang; Qiang-Sheng Wu; Xin-Hua He (Mycorrhiza, 2015)

Arbuscular mycorrhiza mediates glomalin-related soil protein production and soil enzyme activities in the rhizosphere of trifoliate orange grown under different P levels - Qiang-Sheng Wu; Yan Li; Ying-Ning Zou; Xin-Hua He (Mycorrhiza, 2015)

Soil fertility and its significance to crop productivity and sustainability in typical agroecosystem: a summary of long-term fertilizer experiments in China - Qingyin Shang; Ning Ling; Xumeng Feng; Xiuxia Yang; Pingping Wu; Jianwen Zou; Qirong Shen; Shiwei Guo (Plant and Soil, 2014)

Heat shock factor OsHsfB2b negatively regulates drought and salt tolerance in rice - Jianhua Xiang; Jing Ran; Jie Zou; Xiaoyun Zhou; Ailing Liu; Xianwen Zhang; Yan Peng; Ning Tang; Guangyu Luo; Xinbo Chen (Plant Cell Reports, 2013)

Regulatory long non-coding RNA and its functions - Yong Huang; Ning Liu; Jian Ping Wang; Yu Qin Wang; Xue Li Yu; Zhan Bin Wang; Xiang Chao Cheng; Quan Zou (Journal of Physiology and Biochemistry, 2012)

Contributions of arbuscular mycorrhizal fungi to growth, photosynthesis, root morphology and ionic balance of citrus seedlings under salt stress - Qiang-Sheng Wu; Ying-Ning Zou; Xin-Hua He (Acta Physiologiae Plantarum, 2010)

Effects of high dietary fat and cholesterol on expression of PPARα, LXRα, and their responsive genes in the liver of apoE and LDLR double deficient mice - Yanyan Zou; Hui Du; Miao Yin; Liang Zhang; Liufeng Mao; Ning Xiao; Guocheng Ren; Cong Zhang; Jie Pan (Molecular and Cellular Biochemistry, 2009)

Expression, purification and characterization of a phyA m -phyCs fusion phytase - Li-kou Zou; Hong-ning Wang; Xin Pan; Guo-bao Tian; Zi-wen Xie; Qi Wu; Hui Chen; Tao Xie; Zhi-rong Yang (Journal of Zhejiang University-SCIENCE B, 2008)

Osmotic solute responses of mycorrhizal citrus (Poncirus trifoliata) seedlings to drought stress - Qiang-Sheng Wu; Ren-Xue Xia; Ying-Ning Zou; Gui-Yuan Wang (Acta Physiologiae Plantarum, 2007)

Light-path length and population density in photoacclimation of Nannochloropsis sp. (Eustigmatophyceae) - Ning Zou; Amos Richmond (Journal of Applied Phycology, 2000)

Efficient utilisation of high photon irradiance for mass production of photoautotrophic micro-organisms - Amos Richmond; Ning Zou (Journal of Applied Phycology, 1999)